2010
DOI: 10.1002/ejoc.201000321
|View full text |Cite
|
Sign up to set email alerts
|

4‐Isoxazolines: Scaffolds for Organic Synthesis

Abstract: This review provides coverage of the more relevant contributions to the synthesis and reactivity of 4‐isoxazolines (2,3‐dihydroisoxazoles). The richness of the reactivity of these heterocycles makes them interesting building blocks for the synthesis of both cyclic and acyclic compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(24 citation statements)
references
References 83 publications
0
24
0
Order By: Relevance
“…The chemistry of three-membered ring heterocycles, especially aziridines, has attracted the attention of synthetic chemists for more than a century because of its ability of acting as versatile species in organic synthesis [11][12][13][14][15]. Baldwin et al have shown that 1,3-dipolar cycloaddition reactions of nitrones to alkynes lead to 4-isoxazolines which rearrange easily under thermal conditions to acylaziridine [16][17][18]. As a part of our ongoing research programme to develop new methodologies in organic synthesis [19][20][21][22], herein, we report synthesis of some new bis(isoxazoline) derivatives (2) from terepthaldehyde in good to excellent yields under microwave irradiation (Scheme 1, Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…The chemistry of three-membered ring heterocycles, especially aziridines, has attracted the attention of synthetic chemists for more than a century because of its ability of acting as versatile species in organic synthesis [11][12][13][14][15]. Baldwin et al have shown that 1,3-dipolar cycloaddition reactions of nitrones to alkynes lead to 4-isoxazolines which rearrange easily under thermal conditions to acylaziridine [16][17][18]. As a part of our ongoing research programme to develop new methodologies in organic synthesis [19][20][21][22], herein, we report synthesis of some new bis(isoxazoline) derivatives (2) from terepthaldehyde in good to excellent yields under microwave irradiation (Scheme 1, Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…[2] Although copper nitrate has been disclosed as an effective direct nitration reagent for arenes [3] and ketones, [4] theu se of this simple and inexpensive reagent as an ew and versatile nitrogen and oxygen source to replace the traditionally required agents still remains both challenging and of great value. D 2 -Isoxazoline derivatives represent an important class of five-membered heterocycles [5] and are frequently found in numerous biologically active molecules with antibacterial, [6a] antitubercular, [6b] siderophore, [6c] antidepressant, [6d] and b-galactosidase-inhibiting properties.…”
mentioning
confidence: 99%
“…Synthesis of aziridines 3 and 4. (2015) 1e4 2 under thermal activation [10]. Nevertheless, the ringopening rearrangement can also be triggered by Cu(I)-species [11] or under radical conditions using Co 2 (CO) 8 [12].…”
Section: Resultsmentioning
confidence: 98%